Pharmacometric and electrocardiographic evaluation of chloroquine and azithromycin in healthy volunteers - Chotsiri, P; Tarning, J; Hoglund, RM; Watson, JA; White, NJ (American Society for Clinical Pharmacology and Therapeutics, 2022)
Chloroquine and azithromycin were developed in combination for the preventive treatment of malaria in pregnancy, and more recently were proposed as coronavirus disease 2019 (COVID-19) treatment options. Billions of doses of chloroquine have been administered worldwide over the past 70 years but concerns regarding cardiotoxicity, notably the risk of torsades de pointes (TdP), remain. This investigation aimed to characterize the pharmacokinetics and electrocardiographic effects of chloroquine and azithromycin observed in a large previously conducted healthy volunteer study. Healthy adult volunteers (n = 119) were randomized into 5 arms: placebo, chloroquine alone (600 mg base), or chloroquine with either 500 mg, 1,000 mg, or 1,500 mg of azithromycin all given daily for 3 days. Chloroquine and azithromycin levels, measured using liquid-chromatography tandem mass spectrometry, and electrocardiograph intervals were recorded at frequent intervals. Time-matched changes in the PR, QRS, and heart rate-corrected JT, and QT intervals were calculated and the relationship with plasma concentrations was evaluated using linear and nonlinear mixed-effects modeling. Chloroquine and azithromycin pharmacokinetics were described satisfactorily by two- and three-compartment distribution models, respectively. No drug–drug interaction between chloroquine and azithromycin was observed. Chloroquine resulted in concentration-dependent prolongation of the PR, QRS, JTc and QTc intervals with a minimal additional effect of azithromycin. QRS widening contributed ~ 28% of the observed QT prolongation. Chloroquine causes significant concentration-dependent delays in both ventricular depolarization and repolarization. Co-administration of azithromycin did not significantly increase these effects. The arrhythmogenic risk of TdP associated with chloroquine may have been substantially overestimated in studies which did not separate electrocardiograph QRS and JT prolongation.